1990
DOI: 10.1002/jcp.1041430123
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐associated modifications of low‐molecular‐weight thiols and protein sulfhydryls in human bronchial fibroblasts

Abstract: The thiol redox status of cultured human bronchial fibroblasts has been characterized at various growth conditions using thiol-reactive monobromobimane, with or without the combination of dithiotreitol, a strong reducing agent. This procedure has enabled measurement of the cellular content of reduced glutathione (GSH), total glutathione equivalents, cysteine, total cysteine equivalents, protein sulfhydryls, protein disulfides, and mixed disulfides. Passage of cells with trypsin perturbs the cellular thiol home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 35 publications
(35 reference statements)
3
36
0
Order By: Relevance
“…Firstly, V79 cells are known to share GSH through intercellular contacts, enhancing GSH content heterogeneity between cells at low cell density [44]. Second, Atzori et al [45] observed that trypsin treatment of human bronchial fibroblasts transiently affected GSH content. Lastly, a detailed study on GGT expression as a function of cell density led to a lower GGT specific activity after 24-h growth.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, V79 cells are known to share GSH through intercellular contacts, enhancing GSH content heterogeneity between cells at low cell density [44]. Second, Atzori et al [45] observed that trypsin treatment of human bronchial fibroblasts transiently affected GSH content. Lastly, a detailed study on GGT expression as a function of cell density led to a lower GGT specific activity after 24-h growth.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Many studies involving lymphocytes and fibroblasts showed that an increased GSH level was associated with an early proliferative response and was essential for the cell to enter the S phase. 2,4,7,8 We showed previously that plating primary cultures of rat hepatocytes under low density, which stimulates hepatocytes to shift from the G 0 to the G 1 phase of the cell cycle, resulted in increased levels of GSH and cysteine, and increased activity of ␥-glutamylcysteine synthetase (GCS), the rate-limiting enzyme in GSH synthesis, as early as 4 hours after plating.…”
mentioning
confidence: 99%
“…thiol residue status) are most likely the main regulatory processes besides phosphorylation (36). Evidence is now cumulating that cell fate and proliferation depend on its redox status (43)(44)(45)(46). Our study pinpoints a crucial intermediate in the process of redox control of mitochondrial biogenesis and cell growth that is the glutathione redox state.…”
Section: Discussionmentioning
confidence: 71%